Ecologische thematiek in hedendaagse fi ctie: Uitdagingen van milieufi losofi e, ecokritiek en animal studies voor de Nederlandstalige literatuur/ Ecology in the Contemporary Fiction: The Challenges of Environmental Philosophy, Ecocriticism and Animal Studies for the Study of Dutch and Flemish Literature - Sedláčková, Lucie (Werkwinkel, 2015)
This article is based on the belief that in every historical period, there is a certain part of the literary production that reflects the recent events or tendencies in the contemporary society. Using my dissertation, in which I did research on the representations of the globalisation in recent Dutch and Flemish fiction, as an example of which issues were or were not represented in a number of selected Dutch-written novels, I point out that ecology, which turned to be a non-issue in my corpus, deserves new attention at this moment. My article suggests some attitudes that can help to interpret the ecological issues and the tightly connected subject of animal rights. The new challenges for the literary studies are first of all presented by the ecocriticism and the (critical) animal studies